Propensity Score Analysis of Regorafenib Versus Trifluridine/Tipiracil in Patients with Metastatic Colorectal Cancer Refractory to Standard Chemotherapy (REGOTAS): A Japanese Society for Cancer of the Colon and Rectum Multicenter Observational Study. (11th September 2017) - Moriwaki, Toshikazu; Fukuoka, Shota; Taniguchi, Hiroya; Takashima, Atsuo; Kumekawa, Yusuke; Kajiwara, Takeshi; Yamazaki, Kentaro; Esaki, Taito; Makiyama, Chinatsu; Denda, Tadamichi; Satake, Hironaga; Suto, Takeshi; et al.
Abstract : Background: This study compared the efficacy of regorafenib and trifluridine/tipiracil (TFTD) in patients with metastatic colorectal cancer (mCRC) who are refractory to standard chemotherapy, because despite their clinical approval, it still remains unclear which of these two drugs should be used as initial treatment. Materials and Methods: The clinical data of patients with mCRC who were treated with regorafenib or TFTD and those of drug‐naive patients, between June 2014 and September 2015, were retrospectively collected from 24 institutions in Japan. Overall survival (OS) was evaluated using the Cox's proportional hazard models based on propensity score adjustment for baseline characteristics. Results: A total of 550 patients (223 patients in the regorafenib group and 327 patients in the TFTD group) met all criteria. The median OS was 7.9 months (95% confidence interval [CI], 6.8–9.2) in the regorafenib group and 7.4 months (95% CI, 6.6–8.3) in the TFTD group. The propensity score adjusted analysis showed that OS was similar between the two groups (adjusted hazard ratio [HR], 0.96; 95% CI, 0.78–1.18). In the subgroup analysis, a significant interaction with age was observed. Regorafenib showed favorable survival in patients aged <65 years (HR, 1.29; 95% CI, 0.98–1.69), whereas TFTD was favored in patients aged ≥65 years (HR, 0.78; 95% CI, 0.59–1.03). Conclusion: No significant difference in OS between regorafenib and TFTD was observed in patients with mCRC. Although the choice of the drug by age might affect survival, a clearly predictive biomarker to distinguish the two drugs should be identified in further studies. Implications for Practice: Previous studies of patients with metastatic colorectal cancer refractory to standard chemotherapy had demonstrated that both regorafenib and trifluridine/tipiracil could result in increased overall survival compared with placebo, but there are no head‐to‐head trials. This large, multicenter, observational study retrospectively compared the efficacy of regorafenib and trifluridine/tipiracil in 550 patients with metastatic colorectal cancer refractory to standard chemotherapy who had access to both drugs. Although no difference in overall survival was found between the two drugs in adjusted analysis using propensity score, regorafenib showed favorable survival in patients aged <65 years, whereas trifluridine/tipiracil was favored in patients aged ≥65 years in the subgroup analysis. Abstract : This article compares the efficacy between regorafenib and trifluridine/tipiracil in patients with metastatic colorectal cancer refractory to standard chemotherapy, who had access to both drugs, to determine whether a further prospective comparative trial should be conducted.